2013
DOI: 10.1002/14651858.cd001877.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Screening for breast cancer with mammography

Abstract: Analysis 1.3. Comparison 1 Screening with mammography versus no screening, Outcome 3 Deaths ascribed to breast cancer, 7 years follow up, women below 50 years of age (Malmö 55

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
581
0
80

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 980 publications
(672 citation statements)
references
References 324 publications
11
581
0
80
Order By: Relevance
“…Ironically, increased awareness confers less opportunity for screening mammography to reduce the incidence of advanced cancer. Moreover, retrospective analyses of the trials have revealed deficiencies such as more surgery and radiation in women randomized to be screened and differential misclassification of cause of death in the favor of the screened group [48][49][50].…”
Section: Using [Our] Methods There Is No Evidence Of Overdiagnosis Omentioning
confidence: 99%
“…Ironically, increased awareness confers less opportunity for screening mammography to reduce the incidence of advanced cancer. Moreover, retrospective analyses of the trials have revealed deficiencies such as more surgery and radiation in women randomized to be screened and differential misclassification of cause of death in the favor of the screened group [48][49][50].…”
Section: Using [Our] Methods There Is No Evidence Of Overdiagnosis Omentioning
confidence: 99%
“…There are several publications 11,[28][29][30][31][32][33][34][35][36][37] which have estimated mortality reduction due to breast screening, which are summarized in Table 2. Since the mortality reduction in the population invited to screening found in the literature was mainly 20% with a range of 15-30% in the invited population, this value and range have been used in this work.…”
Section: Published Risk Factors For Risk Of Radiationinduced Cancersmentioning
confidence: 99%
“…Breast cancer is the most common cancer in women, affecting ~12.5% women [29]. Ovarian cancer is the most lethal cancer among women, affecting a~1.4% women [30].…”
Section: Dr David Chuderland From Genesort Ltdmentioning
confidence: 99%